PENDAMPINGAN PENCEGAHAN STUNTING MELALUI PENGOLAHAN PROTEIN NABATI DAN HEWANI DENGAN PANGAN LOKAL DI DESA SENDANGAGUNG - Safitri, Emilia Dani; Febrianti, Eka Ageng; Diokta, Vania Safa; Ramadhan, lham; Hanoum, Haliza; Amalia, Nadila; Muzakka, Feerousah; Marliana, Marliana; Cahyaningrum, Galih Siwi; Anggraheni, Nadia Putri; Suryanto, Syafauzi; Lailatussyuhada, Sri; Sipinta, Leliana Putri; Widyantari, Lusiana; Lestari, Yuli Yani Dwi (Jurnal Abdi Insani, 2025)
Stunting is a growth disorder caused by chronic malnutrition, especially during the first 1,000 days of life. Protein, as one of the main macronutrients, plays a crucial role in muscle and bone growth as well as tissue repair, which can help prevent stunting. Based on observations in Sendangagung Village, 58 out of 375 toddlers monitored were found to be stunted. This condition is caused by a lack of parental knowledge and other factors such as economic, social, and cultural aspects. This community service activity aims to increase public awareness regarding the importance of stunting prevention. In addition, the community is expected to improve their skills in processing plant-based and animal-based proteins using local food sources as a nutritional intervention to prevent stunting. The activity was carried out from July to August 2024 at the Multipurpose Building of Sendangagung Village. Education was delivered through audiovisual presentations using PowerPoint, followed by pre-tests and post-tests. Meanwhile, practical sessions on processing plant-based and animal-based proteins into supplementary foods were conducted participatively by involving all participants directly. The average pre-test score of participants was 10.24, while the average post-test score was 13.36. The results of the paired t-test showed a significance value of 0.000 < 0.05, indicating a significant difference between pre-test and post-test scores. It can be concluded that there was an improvement in participants' knowledge after the counseling and assistance. Moreover, participants were able to process plant-based and animal-based proteins into food products that help prevent stunting. There was an increase in participants' knowledge and skills regarding stunting prevention through local food-based protein processing. Therefore, community assistance is an effective method in efforts to prevent stunting.